Interactions of Transition Metal Ions with DNA: A Review of AFM and FTIR Studies for Structural Insights and Nanostructures Fabrication - Hasan Daw A. Mohamed; Mahmoud A. Abushiba; Amal Guma Saaid; Zenineb M. Khalifa Mohamed (African Journal of Advanced Pure and Applied Sciences, 2025)
DNA possesses a diverse a range of chemical functionalities that allow it to interact with transition metal ions, influencing its structural stability and serving as a valuable template for nanostructure fabrication. This review focuses on the application of Fourier Transform Infrared Spectroscopy (FTIR) and Atomic Force Microscopy (AFM) to explore these interactions. FTIR offers molecular-level insights into how metal ions coordinate with phosphate groups and nitrogenous bases, while AFM visualizes the resulting nanoscale changes in DNA morphology. Investigations of metal ions such as Cu²⁺, Ag⁺, Ni²⁺, Co²⁺, Fe²⁺, Zn²⁺, and Rh³⁺ reveal varying binding behaviors, structural impacts, and potential applications. A comparative analysis of Cu(II) and Ag(I) interactions with DNA demonstrates that copper can cause significant structural disruption and oxidative damage, whereas silver selectively binds to guanine and adenine without inducing major conformational changes. The combined application of FTIR and AFM provides a comprehensive understanding of DNA–metal ion interactions, supporting their use in biosensing, nanowire fabrication, DNA-templated nanoparticles, and the development of metal-based therapeutic agents.